Realism, Nominalism and How Probable the Disappearance of Accounting Profession is - N. A. Mislavskaja (Учёт. Анализ. Аудит, 2018)
One of the characteristic features of twenty-year period of reforming the national system of accounting is that the new results of scientifc research opposing the principles of international fnancial reporting standards are not included in accounting practice. A false idea about the universal character of the IFRS, total conformism of accounting professional community and the shift to practically-oriented approach in the curricula of higher education institutions resulted in discrediting of accounting knowledge. Modern methodological approaches of economics in relation to accounting and fnancial reporting are inclined to consider the latter as applied secondary tool of generating fnancial information. From historical and objective point of view the very task of accounting was to provide such information that would aid in making educated and effective managerial decisions and later to increase or at least preserve the capital. Pursuing this goal the methodology (in addition to particular methods) has been going through changes depending on the goals set by the users of fnancial information. After the IFRS had been introduced the process of methodology transformation gained a one-way character — “everything should conform to the IFRS” —and consequently accounting as a tool which takes into account constantly changing goals, for example the goals set by the state, stopped working. This resulted in the compromise of accounting. In order to clarify the reasons of the above the article analyses the stages of the development of ideas, approaches and directions in economic theory, identifes its links with the evolution of science and retrospectively matches the peculiarities of the latter with such methodological directions of philosophy of science as nominalism and realism. The motivated rationale of the crucial importance to classify the stages of scientifc knowledge development determines the strategic choice of the methods of the research: deduction, information analysis; abstracting; dialectic logic of making conclusions and proposals. The result of the research is the rationale of the processes of historical development of accounting science, identifcation of logical correlation between the ideology of economic theory classical scholars and methodology of accounting knowledge. The author proposes to treat the contemporary history of the issue by introducing such terms as political and demagogical nominalism in conceptual construct.